Analytical study on the mechanical performance of composite sandwich shells for dielectric radar domes. (January 2017) - Alankaya, Veysel
Radar domes are the cover structures over the radar antenna systems to provide environmental protection to the sensitive parts such as electronics, steering hardware, wave guide, additional equipments, and antenna itself. Composite dielectric materials are preferred solutions for radome construction because of their negligible effects on electromagnetic transmission of enclosed antenna. Very recently, the effect of interlaminar stress distribution and radome geometry over the transmission capabilities is reported by several researchers. The aim of this study is to present an efficient solution methodology with minimized mathematical effort for the analytical solution of sandwich composite dielectric materials for radome structures with one and double core layers. Analytical solution methodology for the analyses of stresses and deformations is based on Third-Order Shear Deformation Theory (TSDT). Double Fourier series which are specialized for boundary discontinuity are used to solve highly coupled linear partial differential equations. Numerical solutions for the designed spherical radome geometry with one and double core layers are presented for laminated sandwich shells to provide benchmark results for the pre-design activities of radome structures.